High-Flow Nasal Oxygen versus Noninvasive Ventilation in Acute Exacerbation of Chronic Obstructive Pulmonary Disease Patients: A Meta-Analysis of Randomized Controlled Trials - Yanping Du; Huaping Zhang; Zhiyi Ma; Jun Liu; Zhiyong Wang; Meixia Lin; Fayu Ni; Xi Li; Hui Tan; Shifan Tan; Yanling Chai; Xiangzhu Zhong (Canadian Respiratory Journal)
Background. High-flow nasal cannula (HFNC) can be used in stable chronic obstructive pulmonary disease (COPD) patients, but the effect of HFNC on clinical outcomes in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is still uncertain. Methods. We searched electronic literature databases for randomized controlled trials (RCTs) comparing HFNC with noninvasive ventilation (NIV) in hypercapnic patients with AECOPD. The primary endpoint of this meta-analysis was PaCO2, PaO2, and SpO2. The secondary outcomes were the respiratory rate, mortality, complications, and intubation rate. Results. We included 7 RCTs with a total of 481 patients. There were no significant differences on measures of PaCO2 (MD = −0.42, 95%CI −3.60 to 2.75, Z = 0.26, and P = 0.79), PaO2 (MD = −1.36, 95%CI −4.69 to 1.97, Z = 0.80, and P = 0.42), and SpO2 (MD = −0.78, 95%CI −1.67 to 0.11, Z = 1.72, P = 0.08) between the HFNC group and the NIV group. There was no significant difference in measures of the mortality and intubation rate between the HFNC group (OR = 0.72, 95%CI 0.30 to 1.69, Z = 0.76, and P = 0.44) and the NIV group (OR = 2.38, 95%CI 0.49 to 11.50, Z = 1.08, and P = 0.28), respectively. But the respiratory rate in the HFNC group was lower than that in the NIV group (MD = −1.13, 95%CI −2.13 to −0.14, Z = 2.23, and P = 0.03), and fewer complications were found in the HFNC group (OR = 0.26, 95%CI 0.14 to 0.47, Z = 4.46, and P < 0.00001). Conclusion. NIV was noninferior to HFNC in decreasing PaCO2 and increasing PaO2 and SpO2. Similarly, the mortality and intubation rate was similar among the two groups. The respiratory rate and complications were inferior in the AECOPD group treated with HFNC.